Effects of pH and different sugars on the structures and emulsification properties of whey protein isolate-sugar conjugates. (February 2020) - Xi, Chunyu; Kang, Naixin; Zhao, Changhui; Liu, Yujia; Sun, Zhengwei; Zhang, Tiehua
Abstract: Glycosylation is one of the more studied methods used to improve the emulsification properties of proteins, and glycosylation products are often used as transport carriers for nutrients. In this study, we investigated the structure and emulsifying properties of whey protein isolate (WPI)-sugar conjugates formed with different sugars (glucose, lactose, and dextran) under different pH (2–10) conditions. The results show that pH affected the degree of glycosylation (DG), and alkaline environments were conducive to the formation of WPI-sugar conjugates. As the pH increased from 6 to 10, the protein unfolded, DG, apparent viscosity and emulsifying properties increased. At pH 8–10, the free sulfhydryl content of the WPI-sugar conjugates decreased, disulfide bonds formed, aggregation occurred between protein molecules, the DG, surface hydrophobicity and apparent viscosity decreased, thus the emulsion stability decreased. Different sugars had an effect on DG, with glucose increasing the DG and decreasing surface hydrophobicity and free sulfhydryl content. Dextran increases the apparent viscosity and emulsifying properties of the WPI-sugar conjugates. Therefore, it can be concluded that pH affected the structure and emulsifying properties of the WPI-sugar conjugates, pH has a certain effect on the secondary and tertiary structures of the WPI, the DG and emulsifying properties being better for conjugates formed in alkaline environments. Different sugars affected the emulsifying properties and surface structures of the WPI-sugar conjugates, but had little effect on the secondary and tertiary structures. Highlights: This paper studied the effect of pH during the glycosylation reaction process and different sugars on the structure and emulsification properties of whey protein isolate-sugar conjugates. By changing the pH of the glycosylation reaction process and different sugars, the emulsification properties of the protein can be adjusted, which has high application value in the field of fat-soluble nutrient transport.